Extending the Technology Acceptance Model for E-learning Discussion Forum Adoption - Louw, Jenny; Swart, Arthur J; Bere, Aaron (African Engineering Education Association Conference, CUT, FS, 2016)
The advancement on Information and Communication Technology and the Internet for educational purposes has been a staple discourse among researchers in recent years. However, preliminary investigations indicate that e-learning systems are underutilized due to the fact that some of their major features remaining inactive; features like electronic discussion forums. Despite several scholars reporting on high levels of e-learning systems implementation at Universities of Technology (UoT), it is disconcerting that discussion forums within these platforms remain poorly utilized. The purpose of this study is to establish constructs that may promote adoption and use of discussion forums. The Technology Acceptance Model forms the theoretical framework for this study and is extended by including digital inclusion, perceived attention and perceived enjoyment. Thirty participants were purposively selected from a third year Information Technology class and interviewed with regards to the different constructs which make up the Technology Acceptance Model. Findings of this case study suggest that, perceived usefulness and ease along with digital inclusion may positively influence adoption and use of discussion forums at UoT. The study contributes to the board of knowledge by providing useful insights into the application of the Technology Acceptance Model by establishing additional constructs that may promote discussion forum usage.
Published Conference Proceedings
Keywords: e-learning; LMS; Blackboard; Digital inclusion; Perceived attention